EFFECTIVENESS OF TOMATO AS TRAP CROP FOR LIRIOMYZACHINENSISKATO (DIPTERA : AGROMYZIDAE)AND ITS PARASITOID ON RED ONION CROPS ( ALLIUM CEPAVARAGGREGATUM - Ni Putu Sukarini; Shahabuddin Shahabuddin; Hasriyanti Hasriyanti (Tadulako University, 2017)
This research aimed to find out the effectiveness of tomatoes as a trap crop to control liriomyzachinencis, the leaf cutter pest s and its parasitoids on onion plants varieties with a different planting time at Palu valley.This research was conducted on June until August 2015 in Langaleso village, west Dolo of Sigibiromaru Regency, central Sulawesi procince. Also futher research was conducted at the laboratory of pest and plant disease of agriculture faculty, tadulako university palu. This research applied an experimental research design by using cluster random sampling. It was treated with one kind of trap crop (tomatoes) with four different planting time, namely : 0, 2, 4, and 6 weeks before the onion being planted. The parameters observed was a kind of liriomyzachinensis, amount of excavation, and the abundance of parasitoid at the level of parasitism. The results of thi research showeded the average number of excavation liriomyzachinencis on the control plants on the eighth week was higher than average number of excavation liriomyzachinencis on the other plants which was given a trap crop treatment. There were two species of parasitoids found on the research area, namely Hemiptarsnusvaricornis and Opius sp. With a level of parasitism which range 23% until 27%.